Perinuclear lens retrodots: a role for ascorbate in cataractogenesis. Issue 2 (February 1987) - Bron, A J; Brown, N A
Abstract : Lens retrodots are round, oblong, or oval features in the perinuclear zone of the adult lens after the fifth decade of life and associated with cataract. Retrodots were found in 47 out of 121 eyes with cataract (39%) in the present series. They show birefringence in vivo and in vitro, and chemical studies suggest that they contain calcium oxalate. It is proposed that ascorbic acid, which is abundant in the normal human lens, is the most likely source for this oxalate. Ascorbic acid is thought to have a protective role against oxidative stress in the lens and other parts of the eye, and its level is known to be reduced in senile cataract. The presence of the retrodots may identify lenses which have been exposed to oxidative stress and are less capable of resisting oxidative damage.